Morphotype diversity of Prorocentrum lima in the western part of Indonesian waters - Riani Widiarti; Neviaty Putri Zamani; Dietriech Geoffrey Bengen; Hawis Madduppa (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Widiarti R, Zamani NP, Bengen DG, Madduppa H. 2021. Morphotype diversity of Prorocentrum lima in the western part of Indonesian waters. Biodiversitas 22: 609-616. Prorocentrum lima is one of the toxic benthic dinoflagellates, known to produce various toxins, including okadaic acid and dinophysis toxins. The species have a wide range of morphological variability, and possess morphotype diversity, which makes it essential to have detailed morphology observation for identification and other purposes. However, such comprehensive observation has never been reported from Indonesian waters. This study aims to determine the morphological characteristics (including pore size and number of pores) of P. lima morphotypes, in the western part of Indonesian waters (Bintan Island, Belitung Island, Seribu Islands, and Karimunjawa Islands). The results showed three different and unique morphotypes of P. lima, namely morphotype 1, morphotype 2, and morphotype 3. Three clusters were presented by Cluster Analysis, corresponded to the three morphotypes, which were Belitung Island clusters, Seribu Islands and Karimunjawa Islands cluster, and Bintan Island cluster, respectively. These findings support distribution of P. lima and its potential risk of toxicity in Indonesian waters, which prompts the necessity of conducting future research, to avoid the negative impact.